2015
DOI: 10.1039/c4ay02289k
|View full text |Cite
|
Sign up to set email alerts
|

A novel fluorescence and resonance Rayleigh scattering probe based on quantum dots for the detection of albendazole

Abstract: Glutathione (GSH)-capped CdTe QDs with diameters of 3 nm were synthesised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Lately, the research in nanoscience opened an even wider pathway in fluorescence studies involving ion pairing. Quantum dots (QDs) are prone to exchange electrons with their complementary partners (acceptors or donors) upon excitation that can be transduced into detectable fluorescent signals [70]. Thus, sensitive assay methods can be developed by using QDs capped with different ligands in ionized form.…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, the research in nanoscience opened an even wider pathway in fluorescence studies involving ion pairing. Quantum dots (QDs) are prone to exchange electrons with their complementary partners (acceptors or donors) upon excitation that can be transduced into detectable fluorescent signals [70]. Thus, sensitive assay methods can be developed by using QDs capped with different ligands in ionized form.…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…An example is the determination method developed for albendazole, using glutathione-capped cadmium telluride QDs (GSH-CdTe QDs). Ion-pair equilibrium takes place between albendazole in cationic form and anionic sites at the QD surface, and the effect was a decrease of the fluorescence intensity of capped CdTe QDs [70].…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…19 presented an ultrasensitive colorimetric/fluorescent sensor to detect Hg 2+ , and the detetion limits of the two modes were both below 10 nM. RRS, a convenient and sensitive molecular spectroscopy, can combine with fluorescence to develop some sensitive fluorescence and RRS dual-model methods 21,22 . For example, based on the changes of fluorescence and RRS intensity after the addition of albendazole (ABZ) to CdTe quantum dots system, Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, based on the changes of fluorescence and RRS intensity after the addition of albendazole (ABZ) to CdTe quantum dots system, Li et al . proposed a dual-model fluorescence/RRS technique to determine ABZ with the DL of nanogram level 21 . Fu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicated it as having antitumor effect in various forms of cancer [18] and Alzheimer disease [29]. Thus, elucidation of action mechanism, obtaining pharmaceutical forms with controlled release [15] and development of new rapid and sensitive assay methods are studies of great interest [12]. The completion of the analytical profile of pharmaceutical substances with the ability to form ion pairs with various counterions is useful mainly for drug control but also for pharmaceutical technology, by obtaining new formulations with predictable biodisponibility, and in pharmacological studies, ion pairing being one of the mechanisms of the absorption [6].…”
Section: Introductionmentioning
confidence: 99%